Study on the effect of mesenchymal stem cells on neural injury, inflammation and copper content in Wilson disease - Zhou, Xiang-xue; Qin, Hao-ling; Chen, Dingbang; Liao, Jian; Liu, Yinjie (Frontiers in Cellular Neuroscience, 2025)
ObjectiveTo investigate the effects of bone marrow mesenchymal stem cells (BMSCs) on extrapyramidal neural network of Wilson disease (WD).Methods27 6-month-old toxic milk mice (TX mice, WD animal model) and 15 C57 mice were selected. Corrected phase (CP) value on susceptibility weighted imaging (SWI), fractional anisotropy (FA) on diffusion tensor imaging (DTI) were performed. The volume of fiber connections was determined. BMSCs was transplanted though tail vein injection (1 × 106, 0.5 mL). The myelin basic protein (MBP), amyloid precursor protein (β-APP), nitric oxide (NO), glutathione (GSH) and interleukin (IL-1β) were determined at 1, 2, 4 and 8 weeks after transplantation.ResultsThe CP value of TX mice increased at 4 (p = 0.029) and 8 weeks (p = 0.037) after transplantation. FA values (p = 0.026, 0.020, 0.037) and the volume of neural fibers (p = 0.016, 0.023, 0.018) increased at 2, 4 and 8 weeks after transplantation. The pathological indexes of demyelination (MBP) and axon injury (β-APP) improved after BMSCs transplantation. The brain copper content decreased at 4 and 8 weeks after transplantation (p = 0.024, 0.038). The indexes of oxidative stress (NO and GSH) and inflammation (IL-1β) of TX mice were improved after transplantation.ConclusionBMSCs can ameliorate WD extrapyramidal neural network injury. The mechanism may be related to reducing copper deposition and alleviating oxidative stress and inflammatory response.